The articular cartilage: Structure and pathologies, and electrical fields as a therapeutic alternative. A Review of current concepts - Vaca-González, Juan Jairo; Gutiérrez, María Lucía; Garzón-Alvarado, Diego Alexánder (Revista Colombiana de Ortopedia y Traumatología, 2017)
Degenerative pathologies that induce morphological, molecular and biomechanical damages in articular cartilage lead to the biochemical reorganisation of the extracellular matrix, affecting the main molecules, such as collagen type II and aggrecan. In pursuit of therapeutic options, electric fields have been useful as treatment for articular cartilage pathologies. These increase cellular viability and stimulate proliferation and expression of proteins such as collagen type II and the aggrecan core protein. This review focuses on the morphology and physiology, pathologies, and treatments of the articular cartilage, emphasising the importance of using electric fields to stimulate articular chondrocytes cultures. In conclusion, it is shown that electric fields increase cell viability and stimulate proliferation and synthesis of major molecules in the cartilage extracellular matrix. This has implications from a therapeutic point of view for the development of novel applications in tissue engineering and regenerative medicine. Evidence level. IV.